Cost-Effectiveness of Robotic Surgery for Rectal Cancer Focusing on Short-Term Outcomes. Issue 22 (June 2015) - Kim, Chang Woo; Baik, Seung Hyuk; Roh, Yun Ho; Kang, Jeonghyun; Hur, Hyuk; Min, Byung Soh; Lee, Kang Young; Kim, Nam Kyu; Banswal., Lalit
<x xml:space="preserve">Abstract</x> Abstract Although the total cost of robotic surgery (RS) is known to be higher than that of laparoscopic surgery (LS), the cost-effectiveness of RS has not yet been verified. The aim of the study is to clarify the cost-effectiveness of RS compared with LS for rectal cancer. From January 2007 through December 2011, 311 and 560 patients underwent totally RS and conventional LS for rectal cancer, respectively. A propensity score-matching analysis was performed with a ratio of 1:1 to reduce the possibility of selection bias. Costs and perioperative short-term outcomes in both the groups were compared. Additional costs due to readmission were also analyzed. The characteristics of the patients were not different between the 2 groups. Most perioperative outcomes were not different between the groups except for the operation time. Complications within 30 days of surgery were not significantly different. Total hospital charges and patients' bill were higher in RS than in LS. The total hospital charges for patients who recovered with or without complications were higher in RS than in LS, although their short-term outcomes were similar. In patients with complications, the postoperative course after RS appeared to be milder than that of LS. Total hospital charges for patients who were readmitted due to complications were similar between the groups. RS showed similar short-term outcomes with higher costs than LS. Therefore, cost-effectiveness focusing on short-term perioperative outcomes of RS was not demonstrated.